2013
DOI: 10.1155/2013/590524
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Mode Control with State Derivative Output Feedback in Reciprocal State Space Form

Abstract: This paper investigates the novel sliding mode control design with state derivative output feedback in nontraditional reciprocal state space (RSS) form. The concepts and the need of RSS form are comprehensively reviewed and explained. Novel switching function and approaching condition based on the derivative of sliding surface are introduced. In addition, a sufficient condition for finding the upper bound of system uncertainty to guarantee the stability in sliding surface is developed for robustness analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…To provide supplementary design algorithms for systems which cannot be modeled in standard state space form and to utilize direct state derivative measurement feedback in control designs in similar ways as state measurement feedback control designs in standard state space form, the following novel reciprocal state space (RSS) form was proposed [14] [15]. When the matrix F in (3) is non-singular (full rank) and only state derivatives are directly measured and fed back, the system can be expressed in reciprocal state space (RSS) form as follows.…”
Section: Mq Dq Kq Bumentioning
confidence: 99%
See 3 more Smart Citations
“…To provide supplementary design algorithms for systems which cannot be modeled in standard state space form and to utilize direct state derivative measurement feedback in control designs in similar ways as state measurement feedback control designs in standard state space form, the following novel reciprocal state space (RSS) form was proposed [14] [15]. When the matrix F in (3) is non-singular (full rank) and only state derivatives are directly measured and fed back, the system can be expressed in reciprocal state space (RSS) form as follows.…”
Section: Mq Dq Kq Bumentioning
confidence: 99%
“…It also showed that applying state derivative feedback in RSS form can easily carry out some popular control design techniques such as pole placement, eigenstructure assignment, and linear quadratic regulator (LQR) [14] [17]. Note that some singular systems with impulse mode can also be expressed in RSS form to easily carry out state derivative measurement feedback control designs [15] [17].…”
Section: From (4a)mentioning
confidence: 99%
See 2 more Smart Citations
“…It is obvious that singular system cannot be expressed in state space form to carry out control design. To provide supplementary design algorithms of state derivative feedback in state space form and handle some of singular systems, a direct state derivative feedback control scheme was developed in "Reciprocal state space" (RSS) form [9] [11][12][13][14][15] by the author of this paper. If F in (2) is invertible, we can have the following system in RSS form and carry out control design with state derivative feedback.…”
Section: Introductionmentioning
confidence: 99%